2015
DOI: 10.1159/000433509
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for Selecting an Optimal Device for the Contralateral Ear of Children with a Unilateral Cochlear Implant

Abstract: Objective: To identify clinical criteria for selecting the aiding device for the contralateral ear of children with a unilateral cochlear implant (CI). Methods: Sixty-five children, including 36 bilateral CI users and 29 bimodal users, participated in the study. A speech perception test (monosyllabic word test) in noise was administered. The target speech (65 dB sound pressure level) was presented from the front loudspeaker, and noise (10 dB signal-to-noise ratio) was presented from 3 directions: from in front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A recent study on school-aged children reports that better speech recognition in noise can be observed in bimodal users, provided that the residual hearing pure-tone audiometry for frequencies 1 kHz is \90 dB HL. 15 As a consequence, the authors suggest first trying bimodal listening for children with a lowfrequency threshold 90 dB HL in the nonimplanted ear and then choosing a sequential CI only if there is no significant benefit in noise from the bimodal option. Similarly, and possibly for the same reasons, this study showed an inverse correlation between mean aided/unaided threshold and parental satisfaction with the HA performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on school-aged children reports that better speech recognition in noise can be observed in bimodal users, provided that the residual hearing pure-tone audiometry for frequencies 1 kHz is \90 dB HL. 15 As a consequence, the authors suggest first trying bimodal listening for children with a lowfrequency threshold 90 dB HL in the nonimplanted ear and then choosing a sequential CI only if there is no significant benefit in noise from the bimodal option. Similarly, and possibly for the same reasons, this study showed an inverse correlation between mean aided/unaided threshold and parental satisfaction with the HA performance.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation of this discrepancy may be that after hearing restoration within the normal range by the CI, implanted children use their contralateral residual hearing to process the fine temporal structure of sounds, which is complementary to information provided by the CI. A recent study on school‐aged children reports that better speech recognition in noise can be observed in bimodal users, provided that the residual hearing pure‐tone audiometry for frequencies ≤1 kHz is <90 dB HL 15 . As a consequence, the authors suggest first trying bimodal listening for children with a low‐frequency threshold ≤90 dB HL in the nonimplanted ear and then choosing a sequential CI only if there is no significant benefit in noise from the bimodal option.…”
Section: Discussionmentioning
confidence: 99%